TINJAUAN TENTANG BAGIAN AHLI WARIS YANG MENOLAK DALAM PERSPEKTIF HUKUM PERDATA BW (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2016)
Based on the constitution, basically everyone has right to accept heir as stated in the regulation or wills. It means that no one comes into the world without right to accept heir. The chance to accept heir is automatically accepted by the heir firmly even secretly to get the property itself. But the other hand, the fact is different. Some people try to reject the heir. The cause is not really clear explained. But there must be something wrong or serious problem happen, so that someone think hard and consider investigating the property before accepting it. The rejection is set in the regulation which explains about the rejection. All these problems need to be discussed to understand civil inheritance law deeply..